2021
DOI: 10.1177/15248399211009783
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Older Adults’ Perceptions of Falls and Fall Prevention

Abstract: Aim To explore gender differences in older adults’ perceptions about preventing falls. Background Falls are a major problem for older adults and health care systems and a challenge to the aging population. Consideration of older adults’ perceptions of fall prevention is needed to increase their engagement in evidence-based prevention strategies. Method A qualitative analysis of secondary data was performed. Results Three major themes emerged: We’ve Seen It, Women Are Caregivers, and Men Are Analyzing Risks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
(35 reference statements)
4
10
0
Order By: Relevance
“…This finding is supported in previous research in which gender difference themes for perceptions about preventing falls are included: Men are Analyzing Risks and Modifying Behaviors and Women are Caregivers (Patton et al, 2021). Men tend to seek more information from healthcare providers and utilize it in their risk analysis, whereas women voiced more self-efficacy and learning from experiences (Patton et al, 2021). In this study, men emphasized the relevance and importance of the healthcare provider leader and observing positive personal outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is supported in previous research in which gender difference themes for perceptions about preventing falls are included: Men are Analyzing Risks and Modifying Behaviors and Women are Caregivers (Patton et al, 2021). Men tend to seek more information from healthcare providers and utilize it in their risk analysis, whereas women voiced more self-efficacy and learning from experiences (Patton et al, 2021). In this study, men emphasized the relevance and importance of the healthcare provider leader and observing positive personal outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…Men more frequently noted the need for structure and leadership as a positive influence on their motivation to exercise. This finding is supported in previous research in which gender difference themes for perceptions about preventing falls are included: Men are Analyzing Risks and Modifying Behaviors and Women are Caregivers ( Patton et al, 2021 ). Men tend to seek more information from healthcare providers and utilize it in their risk analysis, whereas women voiced more self-efficacy and learning from experiences ( Patton et al, 2021 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Men made greater use of emergency services. These differences may be due to: 1) women may be more proactive in seeking care earlier, 2) the number and type of fall risk factors may differ by gender [ 50 ] (e.g., number of chronic diseases may be higher in women [ 51 ]), and 3) men may be more likely to engage in risk-taking behaviour and overestimate their true ability [ 52 ], and 4) baseline health related quality of life may differ [ 53 ]. In our study, men also demonstrated higher mean health resource utilization costs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the facts point to the need to deepen the understanding of the factors associated with falls according to the sex of the fallers. From this, it is possible to extend this issue to two important points: the creation of methods to identify the risks of falls and the improvement of fall prevention programs specific to each sex [ 21 ].…”
Section: Introductionmentioning
confidence: 99%